Systematics of the Ground State Rotational Band in Even-Even Nuclei with 158 <182 and A >230 - Scheuer, W.; Aisenberg, E. (Naciones Unidas, 1958)
Fil: Scheuer, W. Comisión Nacional de Energía Atómica; Argentina